CLAYUCA: Latin American and Caribbean consortium to support cassava research and development - Ospina Patiño, Bernardo (International Center for Tropical Agriculture, 2001)
During the last 25 years, cassava research in Latin America and the Caribbean (LAC) has been the responsibility of the Centro Internacional de Agricultura Tropical (CIAT) in collaboration with national programs, and has been financed mainly with public-sector funds. At the end of the 1980s, this model was not longer viable due to changes in the world’s socio-economic situation, forcing institutions and countries to organize and establish strategic alliances to continue cassavabased research and development activities. The cassava sector in Latin America and the Caribbean also felt this need. To solve this situation, it was necessary to identify and establish new models for financing and supporting cassava research and development to attend to the interests and needs of different groups of end-users of the technology from both the public and the private sector. It was proposed to form a Consortium to finance and support research and development of cassava, to strengthen the transfer of improved technologies, and to enhance the exchange of experiences, information and technologies among LAC countries. Thus, CLAYUCA was established. The mission of CLAYUCA is to contribute to improving living standards and sustainable natural resource management in regions of LAC where cassava plays an important role in agricultural production systems, through the generation, transfer and exchange of technologies, information and scientific knowledge among public and private sector institutions and farmers in the region. The main objectives are: 1. The organized participation of public and private sector institutions, including universities, non-governmental organizations and farmer groups, in the discussion and identification of priority issues and the definition of a regional research and development agenda for the cassava crop. 2. Execution of collaborative cassava-based research and development activities, with participation of diverse institutions in each member country. 3. Seeking additional financial support to implement research and development activities that could benefit all member countries. 4. Strengthening national capacity in each member country to execute research and development activities at the national level and to participate in activities at the international level. Founding members of the Consortium are Colombia, Cuba, Bolivia, Ecuador and Venezuela, the International Center for Cooperation in Agricultural Research for Development (CIRAD) and CIAT. In each country, the group of participants in activities promoted by the Consortium are composed of institutions from the public and private sector, universities, nongovernmental organizations, farmer groups and other sectors involved in cassava production, processing, commercialization and utilization, training, research and technology transfer. Potential members are all cassava producing countries in LAC, which have the capacity to help finance and execute activities of the Consortium.